902 INCIDENCE, CHARACTERISTICS AND CLINICAL OUTCOMES OF PATIENTS PRESENTING WITH VERSUS WITHOUT CARDIOGENIC SHOCK AND RECEIVING CANGRELOR: AN EXPLORATORY SUBANALYSIS OF THE ICARUS REGISTRY. (15th December 2022) - Scalamera, Riccardo; Benenati, Stefano; Gragnano, Felice; Bertero, Edoardo; Capolongo, Antonio; De Sio, Vincenzo; Musumeci, Giuseppe; Annibali, Gianmarco; Campagnuolo, Salvatore; Galasso, Gennaro; Silverio, Angelo; Belllino, Michele; et al.
Abstract: Aims: To assess the frequency, clinical characteristics, and clinical outcomes of patients presenting with and without cardiogenic shock (CS) among those receiving cangrelor in the peri-percutaneous coronary intervention (PCI) phase. Methods: Consecutive patients treated with cangrelor in 7 Italian institutions were retrospectively enrolled in the ICARUS ("Intravenous CAngrelor in high-bleeding Risk patients Undergoing percutaneouS coronary intervention", NCT05505591) registry. Cardiogenic shock was defined as system hypotension (systolic blood pressure < 90 mmHg) despite adequate volume in presence of clinical or laboratory signs of hypoperfusion. The primary endpoint was net adverse clinical events (NACE), defined as a composite of cardiovascular death, myocardial infarction, stroke, definite or probable stent thrombosis and Bleeding Academic Research Consortium (BARC) 2, 3 or 5 bleeding, at 48 hours. Secondary endpoints were assessed at 48 hours. Major adverse cardiovascular events (MACE), defined as a composite of cardiovascular death, myocardial infarction, stroke, and definite or probable stent thrombosis were evaluated at discharge. Results: Out of 551 patients undergoing PCI with cangrelor between January 2019 and August 2022, cardiogenic shock status was available in 550 (99.9%). Among those, 25 (4.5%) presented with CS. Median age was 67 (59-78) vs. 68 (59-77) years in CS vs. non-CS patients (p=0.767). Female sex (44% vs. 24%, p=0.038), presentation with ST-elevation myocardial infarction (84% vs. 42%, p<0.001) and cardiac arrest (46% vs. 4%, p<0.001) were more frequent in the CS group. Likewise, CS patients had higher rates of femoral access (36% vs. 10%, p<0.001), three-vessel PCI (17% vs. 3%, p=0.007), intra-aortic balloon pump implantation (50% vs. 3%, p<0.001) and Gp IIb/IIIa inhibitors use (16% vs. 3%, p=0.005). At 48 hours, CS patients had higher rates of NACE (44% vs. 7%, p<0.001), MACE (12% vs. 1%, p=0.008), cardiovascular death (12% vs. 0.4%, p=0.001), BARC 2, 3 or 5 bleeding (32% vs. 6%, p<0.001), and BARC 3 or 5 bleeding (16% vs. 1%, p=0.001). At multivariable logistic regression, CS independently predicted the occurrence of NACE (odds ratio [OR] 1.29, 95% CI 1.14-1.45, p<0.001) and BARC 3 or 5 bleeding (OR 1.14, 95% CI 1.08-1.21, p<0.001). In-hospital MACE were available in all but one patient, with an event rate that was higher among CS patients (32% vs. 1.3%, log-rank p<0.001). At Cox multivariable analysis, cardiogenic shock was the only independent predictor of in-hospital MACE (hazard ratio [HR] 7.13, 95% CI 1.37-36.8). Conclusions: Approximately 5% of patients receiving cangrelor in real-world clinical practice presented with CS. These patients were at higher risk of both ischemic and bleeding events. CS independently predicted the occurrence of 48-hour NACE and major bleeding, as well as in-hospital MACE.